Pole lengths influence O2-cost during double poling in highly trained cross-country skiers - Carlsen, C. H.; Rud, B.; Myklebust, H.; Losnegard, T. (European Journal of Applied Physiology, 2018)
Purpose: In elite cross-country skiing, double poling is used in different terrain. This study compared O2-cost and kinematics during double poling with four different pole lengths [self-selected (SS), SS - 5 cm, SS + 5 cm, SS + 10 cm] at Low versus Moderate incline. Methods: Thirteen highly trained male cross-country skiers (mean ± SD 23 ± 3 years; 182 ± 4 cm; 77 ± 6 kg) completed eight submaximal trials with roller skis on a treadmill at two conditions: "Low incline" (1.7°; 4.5 m s-1) and "Moderate incline" (4.5°; 2.5 m/s) with each of the four pole lengths. O2-cost and 3D body kinematics were assessed in each trial. Results: In Low incline, SS + 10 cm induced a lower O2-cost than all the other pole lengths [P < 0.05; effect size (ES) 0.5-0.8], whereas no differences were found between the remaining pole lengths (P > 0.05; ES 0.2-0.4). In Moderate incline, significant differences between all pole lengths were found for O2-cost, with SS - 5 cm > SS > SS + 5 cm > SS + 10 cm (P < 0.05; ES 0.6-1.8). The relative differences in O2-cost between SS and the other pole lengths were greater in Moderate incline than Low incline (SS - 5 cm; 1.5%, ES 0.8, SS + 5 cm; 1.3%, ES 1.0, and SS + 10 cm; 1.9%, ES 1.0, all P < 0.05). No difference was found in cycle, poling or reposition times between pole lengths. However, at both conditions a smaller total vertical displacement of center of mass was observed with SS + 10 cm compared to the other pole lengths. Conclusion: Increasing pole length from SS - 5 cm to SS + 10 cm during double poling induced lower O2-cost and this advantage was greater in Moderate compared to Low incline.